Clinical Patterns of Superficial Fungal Infections in Children Attending Outpatient Department of a Tertiary Hospital in Bangladesh (Mugda Medical College Journal, 2025)
Superficial fungal infections (SFIs) are common skin infections worldwide. These infections significantly affect the health and well-being of children, particularly in a developing country like Bangladesh. Therefore, there is need to provide up-to-date information on this disease for evidence based effective interventions. The aim of the present study was to determine clinical patterns of superficial fungal infections in children attending the outpatient department of Dermatology and Venereology of Mugda Medical College Hospital, Dhaka, Bangladesh. This cross-sectional, descriptive study was conducted from January to June of 2024. A total of 385 children aged £18 years with superficial fungal infections were included in this study. Demographic data, medical history and systemic disease were documented. 10% potassium hydroxide microscopy and Wood’s lamp examination were done when necessary. The groin was the most frequently affected site (41.8%), followed abdomen (24.9%), limbs (23.4%) and face (22.1%). Tinea corporis is the most prevalent type of superficial fungal infections (57.7%), followed by tinea cruris (42.9%), tinea faciei (20.5%), and tinea capitis (16.6%). Tinea capitis, tinea faciei, and cutaneous candidiasis were more prevalent in 0-6 years age group, while tinea corporis, and tinea cruris were more prevalent in 13-18 years age group; the differences were statistically significant (P